2021
DOI: 10.4067/s0718-221x2021000100421
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile-mature wood evaluation along the bole considering the influence of silvicultural treatments

Abstract: Wood used for structural purposes has increased in the last decade in Spain. However, as raw material, wood needs to comply with requirements that are not always present. Knowledge about the wood quality from the trees on the stand is essential for providing feedback to forest managers and for taking the required actions to obtain suitable silviculture treatments. Two of the main wood species used in construction in Spain, Pinus nigra and Pinus sylvestris, have been studied in order to determine the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As described by Román et al (2014), individuals with dimensions similar to those shown, have the potential to produce poles, firewood and rural constructions. Furthermore, juvenile wood is associated with shrinkage and a high probability of warping and cracking in the final products (Ruano and Hermoso, 2021;Ruano et al, 2022). Therefore, they are not regularly integrated into traditional industrial processes.…”
Section: Origin Of Solid Waste Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Román et al (2014), individuals with dimensions similar to those shown, have the potential to produce poles, firewood and rural constructions. Furthermore, juvenile wood is associated with shrinkage and a high probability of warping and cracking in the final products (Ruano and Hermoso, 2021;Ruano et al, 2022). Therefore, they are not regularly integrated into traditional industrial processes.…”
Section: Origin Of Solid Waste Processingmentioning
confidence: 99%
“…Firstly, with regeneration felling, a large volume of biomass from large individuals is planned to be removed; secondly, regeneration release logging plans to remove all adult individuals. High-quality raw material is obtained from these treatments, since intensive silviculture promotes self-pruning and the development of straight stems in the stock (Ruano and Hermoso, 2021). Priority should be given to the plywood industry due to the high quality of the raw material, followed by the sawmill industry for thick and thin diameters.…”
Section: Origin Of Solid Waste Processingmentioning
confidence: 99%
“…"Juvenile wood" has been extensively investigated, and some investigators have considered juvenile wood and corewood to be synonymous terms (e.g., [16]). On the other hand, the transition from juvenile to mature wood during secondary growth has frequently been described as a gradual, rather than well delineated, change in various wood properties, making a transition point difficult to identify clearly [16,[18][19][20]. In contrast, corewood terminates abruptly at a latewood-earlywood boundary and physically is clearly delineated from the surrounding outerwood, particularly after wood has dried.…”
mentioning
confidence: 99%
“…As a result, a tree stem has a consistent core diameter of juvenile wood throughout its length. The proportion of juvenile wood in a tree increases with increasing tree height [72]. Therefore, when trees are felled and bucked, pulpwood, top sawlogs, and thinnings tend to have a much higher content of juvenile wood than butt sawlogs.…”
Section: Juvenile and Mature Woodmentioning
confidence: 99%
“…sawmill that handles small diameter top sawlogs with a bottom diameter less than 21.9 cm under bark. Mora sawdust contains a high proportion of mature wood, while Blyberg sawdust has a high proportion of juvenile wood due to the variations in positions and diameters of sawlogs from which the sawdust is generated [72]. A total of about 2000 tonnes of fresh sawdust was delivered to two pellet factories and processed into wood pellets within a month of delivery.…”
Section: Ripping and Chippingmentioning
confidence: 99%